2002
DOI: 10.1046/j.1365-2214.2002.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping of parents with physically and/or intellectually disabled children

Abstract: The findings can be utilized in developing supportive activities for families with disabled children. By recognizing the coping strategies used by the family, professionals and service providers can find the right ways to support their adaptation. As the role of physicians, nursing staff and other professionals in this process is very important, more attention should be attached to the collaboration between these groups, to enable them to view the situation from the perspective of the whole family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
148
0
19

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(178 citation statements)
references
References 27 publications
11
148
0
19
Order By: Relevance
“…Greeff, Vansteenwegen, and DeMot (2006) Communication thus helps families to attain optimal levels of cohesion and flexibility (Patterson, 2002 This finding was also reported by Taanila, Syrjälä, Kokkonen, and Järvelin (2002), who found that open expression facilitated coping by increasing feelings of togetherness and cooperation. Taanila et al (2002) conducted a study to evaluate the coping strategies employed by families of children with intellectual and physical disabilities in northern Finland, and to determine how families coping well differed from those that did not.…”
Section: Making Meaning Of Adversitysupporting
confidence: 60%
See 2 more Smart Citations
“…Greeff, Vansteenwegen, and DeMot (2006) Communication thus helps families to attain optimal levels of cohesion and flexibility (Patterson, 2002 This finding was also reported by Taanila, Syrjälä, Kokkonen, and Järvelin (2002), who found that open expression facilitated coping by increasing feelings of togetherness and cooperation. Taanila et al (2002) conducted a study to evaluate the coping strategies employed by families of children with intellectual and physical disabilities in northern Finland, and to determine how families coping well differed from those that did not.…”
Section: Making Meaning Of Adversitysupporting
confidence: 60%
“…Taanila et al (2002) found that high-coping families reported that the first diagnosis of their child's disability had been delivered well and that they had also actively sought out further information. These families felt that the knowledge thus gained had facilitated their understanding and acceptance of the situation and enabled them to maintain a positive outlook for the future.…”
Section: First Diagnosis and Information About The Child's Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental emotional reactions to the DCA are expected to be related to their early post-diagnosis emotional adjustment (i.e., psychopathological symptoms), as Taanila, Syrjälä, Kokkonen, and Järvelin (2002) showed that the first moments and days after being informed of their child's disability were critical in determining the family's adaptation process. Several studies described a process of gradual adjustment to the diagnosis (Lalor et al, 2009), although some parents may face difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition to both mortality and morbidity burden of congenital malformations, they have a major impact on the affected families as well as the community as a whole. 2,3 With more focus on the affected communities, it was revealed that the majority of these malformations (up to 94%) occur in middle and low income countries which reflect more closely the seriousness and the major impact of this problem on the affected families and countries. 1,4 The causation of congenital malformation was categorized into four broad categories namely genetic causes, multifactorial, environmental factors and finally the unknown group which constitutes up to 40 to 60 % of all malformations.…”
mentioning
confidence: 99%